Efektifitas Penggunaan Aplikasi Zoom Meeting Dalam Pembelajaran Di Masa Pandemi Covid-19 - Gazali Far-Far (ISTORIA: Jurnal Pendidikan dan Sejarah, 2021)
Abstract: In the current situation, with the threat of Covid-19, it is hoped that educational institutions (university) are required to implement online learning activities. Through the use of the zoom meeting application provided by the university, it is possible to support online learning activities. In essence, this study aims to see to what extent the effectiveness of distance learning using the Zoom Meeting application for students majoring in Social Sciences, FKIP-Unpatti. The method used in this research is qualitative with a grounded theory approach. With data collection techniques used through interviews and WhatsApp for 40 students majoring in Social Sciences FKIP-Unpatti. Based on the research results obtained, distance learning using zoom meetings is certainly not effective during the lecture process. However, considering the current situation with the outbreak of Covid-19, the use of the zoom meeting application is very relevant in supporting the learning process.